Estimation of Strong Ground Motion at Mandalay Region, Myanmar - thein, pyi soe; Khaing, Khaing; Lin, Kyi Kyi; Pramumijoyo, Subagyo; Kiyono, Junji (Journal of Applied Geology, 2025)
Mandalay region lies very closed to the dextral Sagaing fault. In the historical record, several earthquakes happened in and around Mandalay region from the beginning of the year of 1400. Among them the most distinct event is the Sagaing earthquake struck on July 16, 1956. This research mainly focuses on results of microtremor survey at 143 sites and 25 data from the boreholes for determination of sediment thickness characteristics and strong ground motion analysis in Mandalay region. For the accurate prediction of earthquake ground motions, the investigation of three elements in its process, namely the source, path, and site effects, is crucial, and their accuracy and reliability should be evaluated. The subsurface profiles, predominant periods, shear wave velocity structures and information about sediment thickness or depth of engineering bed rock were evaluated based on data from boreholes, microtremor survey and laboratory results, combining with inversion program. The shear wave velocity of the top layer is Vs ≤ 190 m/s. The spectral amplitudes of the estimated strong ground motions were smaller at around 0.5 Hz and larger at around 3 Hz in Mandalay region. The peak ground acceleration becomes more than 0.8 g in some areas, which causes severe damage for buildings in high probability.